(untitled) - Hein, E. K. (Hoboken, N.J., 2007)
The Forensic Mission:Covers crime scene procedures, blood typing, DNA,fingerprints, ballistics, stages of decomposition,and more; Features recaps at the ends of many chapters withvocabulary and background information; Includes two appendixes of additional referencesand Web sites where you can explore chromatography,entomology, forensic pathology, gunshot wounds,and more. You'll be enthralled while you learn in this riveting killer thriller that weaves together bookies, bullets, bodies, and science.
Keywords: Forensic sciences,Forensic sciences,Criminal investigation,Khoa học pháp y,Điều tra hình sự; Fiction,Fiction